Challenges of Health Technology Assessment in Pluralistic Healthcare Systems: An ISPOR Council Report - Drummond, Michael F. (2022)
Health technology assessment (HTA) has been growing in use over the past 40 years, especially in its impact on decisions regarding the reimbursement, adoption, and use of new drugs, devices, and procedures. In countries or jurisdictions with “pluralistic” healthcare systems, there are multiple payers or sectors, each of which could potentially benefit from HTA. Nevertheless, a single HTA, conducted centrally, may not meet the needs of these different actors, who may have different budgets, current standards of care, populations to serve, or decision-making processes. This article reports on the research conducted by an ISPOR Health Technology Assessment Council Working Group established to examine the specific challenges of conducting and using HTA in countries with pluralistic healthcare systems. The Group used its own knowledge and expertise, supplemented by a narrative literature review and survey of US payers, to identify existing challenges and any initiatives taken to address them. We recommend that countries with pluralistic healthcare systems establish a national focus for HTA, develop a uniform set of HTA methods guidelines, ensure that HTAs are produced in a timely fashion, facilitate the use of HTA in the local setting, and develop a framework to encourage transparency in HTA. These efforts can be enhanced by the development of good practice guidance from ISPOR or similar groups and increased training to facilitate local use of HTA.